BURNOUT IN BRAZILIAN HEALTH PROFESSIONALS IN THE COVID-19 PANDEMIC - de Souza, Ana Kainna (2023)
To analyze the scientific evidence on Burnout Syndrome in health professionals in Brazil during the COVID-19 pandemic. Paired integrative review following the PRISMA instrument, identifying 2,096 articles. After excluding duplicates and exclusion criteria, eight articles were read in full, after reading four articles were still excluded, leaving four for the review sample. Prevalence of burnout between 31.6% and 65.5% of respondents. Studies show vulnerabilities in the mental health of professionals, concerns about self-contamination, transmission of the disease and loss of a co-worker or family member, related to physical and mental overload and the long workday that results in high levels of professional exhaustion. Despite the scarcity of specific published studies, the results point to the need for greater attention to mental illness by health professionals in Brazil, especially in the context of a pandemic.